Impact of H2/CH4 blends on the flexibility of micromix burners applied to industrial combustion systems. (1st May 2023) - Lopez-Ruiz, G.; Alava, I.; Blanco, J.M.
Abstract: The present paper investigates the feasibility of using H 2 /CH 4 fuel blends in micromix-type burners applied to industrial combustion systems. The micromix burner concept, characterised by the formation of miniaturised and compact turbulent diffusion flames, was developed for gas turbine hydrogen burners showing low NO x emissions (below 10 ppm) without flashback risk, which represent the main issues when using pure hydrogen or hydrogen enriched natural gas blends as fuel, making it a promising concept to be applied in industrial burners. The study was carried out through numerical CFD simulations, accounting for detailed chemistry calculations of turbulent micromix flames and previously validated through experimental measurements in a laboratory-scale micromix burner prototype. The resulting flow, temperature and exhaust emission characteristics for three H 2 /CH 4 fuel blends with H 2 content of 90, 75 and 60% respectively were analysed and discussed for air–fuel equivalence ratios at λ = 1 . 8 and 1.6 (lower than the well-characterised air–fuel equivalence ratios in micromix gas turbine burners at λ = 2 . 5 and closer to current industrial burners), considering an energy density of 14 MW/m 2 bar. Numerical results showed low fuel flexibility for industrial-scale micromix burners, with still low NO x emissions (12–85 ppm) but relatively high CO emissions (448–4970 ppm) for the considered blends and λ values. The lowest CO emissions were given together with jet penetration phenomena, ruling out the feasibility of these design points due to the greater importance of the latter phenomenon. Highlights: H2/CH4 blends showed low flexibility in micromix burners in off-design operation. Fuel-jet penetration was observed for higher hydrogen concentrations in the fuel. CO values were higher for lower H2 concentrations due to the shorter reaction zones. CO values increased for higher λ caused by shorter residence times.